2016
DOI: 10.3325/cmj.2016.57.474
|View full text |Cite|
|
Sign up to set email alerts
|

Visualization and quantitation of fetal movements by real-time three-dimensional ultrasound with live xPlane imaging in the first trimester of pregnancy

Abstract: AimTo prove whether real-time three-dimensional (3D) ultrasound with live xPlane imaging is better in observing fetal movements than standard ultrasound imaging.Methods50 healthy women with singleton pregnancies (22-43 years old) at 11 to 14 weeks of gestation underwent real-time 3D ultrasound examination with live xPlane imaging from July 2014 to February 2015. The incidence and frequency of 10 fetal movement patterns in 10 minutes were evaluated, including general movements (GMs), isolated arm movements, iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…This is in line with the study of Kuno et al who examined fetal behavior, rest and activity periods, in fetuses at 14-18 weeks GA using 3D ultrasound acquiring images every 1 to 2 s. 22 Promising is the ongoing attempt to expand real-time imaging performing 3D ultrasound, as realized by the group of Lu et al, using two parallel planes for fetal evaluation. 23 However, when we compare our findings and those of de Vries et al, who investigated longitudinally (between 7 and 19 weeks' GA) embryo rest and movement time in 12 healthy nulliparous women by means of 2D transabdominal ultrasound, 24 we find a higher percentage of movement. They found a percentage of movement for nine and 10 weeks' GA of respectively 9% and 17%.…”
Section: Strengths and Limitationssupporting
confidence: 56%
See 1 more Smart Citation
“…This is in line with the study of Kuno et al who examined fetal behavior, rest and activity periods, in fetuses at 14-18 weeks GA using 3D ultrasound acquiring images every 1 to 2 s. 22 Promising is the ongoing attempt to expand real-time imaging performing 3D ultrasound, as realized by the group of Lu et al, using two parallel planes for fetal evaluation. 23 However, when we compare our findings and those of de Vries et al, who investigated longitudinally (between 7 and 19 weeks' GA) embryo rest and movement time in 12 healthy nulliparous women by means of 2D transabdominal ultrasound, 24 we find a higher percentage of movement. They found a percentage of movement for nine and 10 weeks' GA of respectively 9% and 17%.…”
Section: Strengths and Limitationssupporting
confidence: 56%
“…who examined fetal behavior, rest and activity periods, in fetuses at 14–18 weeks GA using 3D ultrasound acquiring images every 1 to 2 s 22 . Promising is the ongoing attempt to expand real‐time imaging performing 3D ultrasound, as realized by the group of Lu et al ., using two parallel planes for fetal evaluation 23 …”
Section: Discussionmentioning
confidence: 99%
“…Foetal movements commence at the first trimester with general movements, followed by breathing movements and head, neck and jaw movements (eg, jaw opening, yawning and sucking) . It has been reported that foetal jaw function is linked to the neck sensorimotor system, with neck movements strongly associated with jaw movements .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, fetal morphology and movement can be assessed using three‐dimensional (3D) and four‐dimensional (4D) ultrasonography; thereby, quantification of fetal activity (such as the timing and frequency of movements throughout development) is becoming more widespread (Lu et al, 2016). Previous studies have shown that fetal movements are first observed between 7‐ and 8.5‐week postmenstrual age (PMA).…”
Section: Introductionmentioning
confidence: 99%